Diastereoselective Coupling of Chiral Acetonide Trisubstituted Radicals with Alkenes. Issue 26 (30th May 2016) - Tao, Daniel J.; Muuronen, Mikko; Slutskyy, Yuriy; Le, Alexander; Furche, Filipp; Overman, Larry E.
Abstract: The stereochemical outcome of reactions of chiral nucleophilic trisubstituted acetonide radicals with electron‐deficient alkenes is dictated by a delicate balance between destabilizing non‐bonding interactions and stabilizing hydrogen‐bonding between substituents on the α and β carbons. Abstract : Connecting the dots : The origins of diastereoselective radical conjugate additions with monocyclic trisubstituted acetonide carbon radicals (see scheme) were investigated both experimentally and computationally.